INTRODUCTION: DEVOLUTION AND SECESSION IN QUESTION. (2022) - Jennings, Colin; Pabst, Adrian
Abstract : This special issue of the National Institute Economic Review is being published at an unsettled and uncertain time for the United Kingdom. In June 2022, the First Minister of Scotland Nicola Sturgeon called for a second referendum on Scottish independence to be held in October 2023. While it is unlikely that the referendum will be granted by the UK government, current polling suggests the outcome of such a referendum would be too close to call. Eight years after Scotland voted 55%–45% to stay in the Union, independence remains a live issue, which raises fundamental questions about economic and governance arrangements between Westminster and the UK's constituent parts.